2012
DOI: 10.1038/mp.2012.85
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study of obsessive-compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a common, debilitating neuropsychiatric illness with complex genetic etiology. The International OCD Foundation Genetics Collaborative (IOCDF-GC) is a multi-national collaboration established to discover the genetic variation predisposing to OCD. A set of individuals affected with DSM-IV OCD, a subset of their parents, and unselected controls, were genotyped with several different Illumina SNP microarrays. After extensive data cleaning, 1,465 cases, 5,557 ancestry-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
256
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(263 citation statements)
references
References 66 publications
5
256
1
1
Order By: Relevance
“…Within this gene, there is a BTB (broad-complex, tramtrack and bric-à-brac) structural domain (amino acids 113-219), a nuclear localization signal region (amino acids 55-70), and a structural domain containing BACK (amino acids 226-335) and PHR (amino acids 226-335) regions. At present, there have been limited studies investigating the function of the BTBD3 gene (13)(14)(15)(16)(17)(18)(19)(20). A previous study by Zhang et al (13), investigating the function of hsa-let-7i in colon cancer metastasis, is the only study to have suggested the BTBD3 gene may be the target of hsa-let-7i.…”
Section: Discussionmentioning
confidence: 99%
“…Within this gene, there is a BTB (broad-complex, tramtrack and bric-à-brac) structural domain (amino acids 113-219), a nuclear localization signal region (amino acids 55-70), and a structural domain containing BACK (amino acids 226-335) and PHR (amino acids 226-335) regions. At present, there have been limited studies investigating the function of the BTBD3 gene (13)(14)(15)(16)(17)(18)(19)(20). A previous study by Zhang et al (13), investigating the function of hsa-let-7i in colon cancer metastasis, is the only study to have suggested the BTBD3 gene may be the target of hsa-let-7i.…”
Section: Discussionmentioning
confidence: 99%
“…DLGAP1, a scaffold-protein-coding gene at the postsynaptic density, is in fact selected for in AMHs and in the horse. This gene has been implicated in obsessive-compulsive disorders and interacts significantly with Shank proteins, mutations in which have been linked to autism spectrum disorders with impaired social interaction and communication [66][67][68] . DLGAP1 interacts with the glutamate receptor GRIK2, implicated in obsessive-compulsive disorders 69 .…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…One of the more consistently replicated genetic findings in OCD is an association with the neuronal glutamate transporter SLC1A1 (protein: EAAT3 or EAAC1) [18][19][20][21][22][23][24] , although a recent meta-analysis showed only a modest association of 2/9 SNPs with OCD 25 , and SLC1A1 has not emerged as a probable locus from recent GWAS studies 15,16 . Findings cluster in the 3′ region, with most evidence for association with the rs301430C allele.…”
Section: Slc1a1mentioning
confidence: 99%